2015
DOI: 10.1111/bjh.13478
|View full text |Cite
|
Sign up to set email alerts
|

Progress in understanding the diagnosis and molecular genetics of macrothrombocytopenias

Abstract: SummaryThe inherited macrothrombocytopenias constitute a subgroup of congenital platelet disorders that is the best characterized from the genetic point of view. This clinically heterogeneous subgroup is characterized by a variable degree of bleeding but without predisposition to haematological malignancies, as seen in the two other subgroups. The classification of inherited thrombocytopenia is traditionally based on the description of different clinical and biological features, in particular the measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 101 publications
0
32
0
Order By: Relevance
“…Classically, enlarged α‐granules are a constant feature of the Paris‐Trousseau syndrome first being seen on stained blood smears and then confirmed by EM . Paris‐Trousseau syndrome results from genetic variants and haplodeficiency of the FLI1 transcription factor, variants that were absent from our families when studied by targeted exome sequencing. For our previously studied patient with the L718del, immunogold labeling and EM clearly showed the association of P‐selectin, αIIbβ3 and fibrinogen with the giant α‐granules suggesting a normal initial granule biosynthesis .…”
Section: Discussionmentioning
confidence: 64%
“…Classically, enlarged α‐granules are a constant feature of the Paris‐Trousseau syndrome first being seen on stained blood smears and then confirmed by EM . Paris‐Trousseau syndrome results from genetic variants and haplodeficiency of the FLI1 transcription factor, variants that were absent from our families when studied by targeted exome sequencing. For our previously studied patient with the L718del, immunogold labeling and EM clearly showed the association of P‐selectin, αIIbβ3 and fibrinogen with the giant α‐granules suggesting a normal initial granule biosynthesis .…”
Section: Discussionmentioning
confidence: 64%
“…ITs are usually asymptomatic, but some individuals may experience excessive bleeding ranging from mild to severe. Over 30 genes are shown to be involved in ITs (Favier and Raslova 2015;Levin et al 2015;Johnson et al 2016a,b;Pecci 2016). One of these, SLFN14, was discovered only very recently where Fletcher et al (2015) identified three heterozygous missense mutations in affected family members from three unrelated families, predicted to encode substitutions K218E, K219N, and V220D within an AAA domain of SLFN14.…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic variants have been associated with CMTP, of which the most frequent alter genes that encode platelet surface proteins and megakaryocyte (MK) cytoskeletal proteins. 2 …”
Section: Introductionmentioning
confidence: 99%